Voice quality in heavy metal singing (Per Musi, 2015)
This paper studies high registers of heavy metal singing based on the voice profile analysis scheme (VPAS) protocol. Its main objective is to provide a scientific basis for a theme which is subjectively treated by the musical literature. Two professional and two amateur singers were recorded for the perceptual analysis. Their vocal productions were analyzed intra- and inter-singers by VPAS experienced judges (vocal coaches, speech therapists, phoneticians). Results indicate that the two groups of singers use distinctive articulatory strategies in singing at high registers.